Carbon dioxide enrichment of PDMS/PSf composite membranes for solving the greenhouse effect and food crisis. (July 2022) - Hu, Chien-Chieh; Lin, Chia-Wei; Hu, Chun-Po; Keshebo, Degu Lere; Huang, Shu-Hsien; Hung, Wei-Song; Lee, Kueir-Rarn; Lai, Juin-Yih
Abstract: Carbon dioxide-enriched air can be used to promote the photosynthesis of plants, accelerate plant growth and fix more carbon dioxide which means that it can solve the food crisis and the greenhouse effect at the same time. The carbon dioxide-enriched air permeance and CO2 concentration in the permeate of the membrane must reach 2000 GPU and 800 ppm to meet the practical needs of accelerating the growth of plants. A polydimethylsiloxane (PDMS)/polysulfone (PSf) composite membrane with appropriate modification that can meet the set goals was successfully prepared. The structure of the membrane selective layer can be precisely adjusted by comprehensively surveying the thickness of the selective layer, the amount of crosslinking agent added, the UV/O3 treatment time and the heat treatment. The carbon dioxide-enriched air permeance and CO2 concentration in the permeate of the modified PDMS/PSf composite membrane reached 2336 GPU and 814 ppm, respectively. In this work, the prepared membrane was also applied to cultivate plants. Comparing Glebionis coronaria grown in an atmospheric environment with Glebionis coronaria grown in CO2 -enriched air, the plant mass and plant height increased by 240% and 40%, respectively, after 4 weeks of growth. Experimental results show that the development of carbon dioxide-enriched PDMS/PSf-modified membranes has strong potential to capture CO2 and accelerate the food production. Graphical Abstract: ga1 Highlight: Modification of the active layer of PDMS membrane using various techniques. To see the impact of CO2 enrichment on plants grown in CO2 -enriched and regular air. The integrated system resulted in reduced greenhouse gas emissions and faster plant growth.